Kualitas silase batang dan daun talas dengan penambahan berbagai aditif silase - Ria Anjalani (Fakultas Peternakan Universitas Kristen Palangka Raya, 2020)
This study aimed to determine the quality of taro stems and leaves silage with the addition of various silage additives. The study used a Completely Randomized Design consisting of 4 treatments namely P1 (5% (w/w) Rice bran), P2 (5% (v/w) Effective Microorganism-4), P3 (5% (w/w) Palm sugar) , and P4 (5% (w/w) Cassava flour) which added based on dry matter. Each treatment used 7 repetitions. The observation parameters in this study were physical quality and chemical quality of silage. Physical quality observations data are described. Chemical quality data were analyzed by analysis of variance. If there were differences among treatments, then further tests are done using Duncan's Multiple Range Test. Physical observation of the silage from the four treatments showed an acidic odor, a brownish-green color, a soft texture, and no fungus. The pH level and Fleigh Score of the four silage treatments showed no significant differences (P> 0.05). The DM content of the four silages showed significant differences (P